Prognostic significance of VEGF‐C, semaphorin 3F, and neuropilin‐2 expression in oral squamous cell carcinomas and their relationship with lymphangiogenesis. Issue 4 (4th December 2014) - Zhang, Bing; Gao, Zhongxiuzi; Sun, Miao; Li, Haixia; Fan, Haixia; Chen, Dong; Zheng, Jinhua
<x xml:space="preserve">Abstract</x> Background Neuropilin‐2 (NRP2), a receptor for vascular endothelial growth factor C (VEGF‐C) and semaphorin 3 F (SEMA3F), is a possible regulator of tumor progression and angiogenesis. However, little evidence of a correlation between NRP2 expression and lymphangiogenesis has been reported. SEMA3F might suppress lymphangiogenesis by competing with VEGF‐C for binding to NRP2. Methods We evaluated lymphatic vessel density (LVD), lymphatic vessel invasion (LVI), the expression levels of VEGF‐C, SEMA3F, and NRP2 by immunohistochemistry in 80 cases of oral squamous cell carcinomas (OSCCs). Results In these tumors, the expression of NRP2 was positively associated with T stage classification, lymph node metastasis, LVD, LVI, and the expression of VEGF‐C. In contrast, low expression of SEMA3F was significantly related to poor differentiation and higher incidence of lymph node metastasis. Patients expressing high levels of VEGF‐C or NRP2, or low levels of SEMA3F had a higher risk of recurrence and shorter overall survival. Multivariate analysis showed that VEGF‐C and NRP2 were independent prognostic markers for overall survival. Conclusions Results indicate SEMA3F is an inhibitor of tumor progression and provide evidence for an association between NRP2 and VEGF‐C, lymphangiogenesis, lymph node metastasis. This suggests the prognostic significance and potential therapeutic value of the VEGF‐C/SEMA3F/NRP2 axis for OSCCs. J. Surg. Oncol. 2015 111:382–388. © 2014 Wiley Periodicals, Inc.